ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY (Studi Empiris pada Perusahaan-Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2012) - Esynasali Violetta Sebayang; Herry Laksito (Diponegoro Journal of Accounting, 2014)
The purpose of this research is to examine the impact of company size, profitability, auditors quality, auditors opinion, and auditors gender influence simultaneously toward audit delay in banking company that listedon the Indonesia Stock Exchange from 2010 to 2012. Sampling method that used is purposive sampling and the result are 27 firms as sample per year. This research is done for 2010-2012 period. Data that used in this research is financial statements from each company, publized through website www.idx.co.id. The data which have already collected are processed with classic assumption test before hypothesis test. Software SPSS version 16.0 is used to test in this research. The results of this study show that of company size and auditors gender is significant effecttoward audit delay, Whereas, profitability, auditors quality, and auditors opinion do not influence time of audit delay.